PERSEPSI PASANGAN USIA SUBUR TERHADAP PELAYANAN KADER POSYANDU DI DESA KASANG LIMAU SUNDAI KABUPATEN KUANTAN SINGINGI - Ade Irma Suriani Irma Suriani; Murni Baheram Baheram; Said Suhil Achmad Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is the lack of services provided by the cadre's in Desa Kasang Limau Sundau Kabupaten Kuantan Singingi. The research problems are how high perception of couples of childbearing age against cadre's services in Desa Kasang Limau Sundau Kabupaten Kuantan Singingi. The purpose of this study was to determine how high the perception of couples of childbearing age against cadre's services in Desa Kasang Limau Sundai Kabupaten Kuantan Singingi. The population in this study as many as 70 people to learn and sample the citizens of this 41 dambil using random sampling techniques. Instrument collecting data questionnaire with 41 statements and after trials, stay 35 valid statement to be made in the research instrument. This type of research is descriptive with quantitative approach. Recapitulation of calculations of mean and SD answers obtained results based on the indicators 1) Selection of 4.57 and 0.75 SD 0,75. 2) preparation by 4.51 and 0.83 SD, and 3) interpretation by 4.51 and 0.87 SD. That is the perception of couples of childbearing age against cadre's service is very high and as expected. Key words: perception, couples of childbearing age, service cadre